2019
DOI: 10.5004/dwt.2019.23838
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of river geomorphology to water quality impact using remote sensing and GIS technique

Abstract: a b s t r a c tRiver plan change is one of the river geomorphology change process. This study focuses on the processes of the river plan change using geographic information system (GIS), remote sensing, and water quality analysis using water quality index (WQI) parameters. Multiple linear regression (MLR) method was used to observe the relationship between river plan change and WQI. Spatial model method was applied along the mainstream of Terengganu River Basin, using GIS to further justify the impact of river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Since fresh water is the most essential component of organic life, a hydrological approach is crucial to improve water resource management for the community. The hydrological field also covers water quality and quantity and the problems that arise in communities that contribute to the problem of environmental pollution and health in a basin [ [1] , [2] , [3] , [4] ]. The problems involved in hydrology are significant from time to time because of problems such as sedimentation, erosion, decreases in river water quality, floods, and other problems that have become the main problems with the river system in Malaysia and all over the world [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…Since fresh water is the most essential component of organic life, a hydrological approach is crucial to improve water resource management for the community. The hydrological field also covers water quality and quantity and the problems that arise in communities that contribute to the problem of environmental pollution and health in a basin [ [1] , [2] , [3] , [4] ]. The problems involved in hydrology are significant from time to time because of problems such as sedimentation, erosion, decreases in river water quality, floods, and other problems that have become the main problems with the river system in Malaysia and all over the world [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies done by researches in Malaysia have demonstrated that several rivers in Malaysia have been contaminated with pollutions conveying from industrial and domestic wastes as well as agricultural and land use runoff along the river [8][9][10][11]. The issues of freshwater pollutions in Malaysia since the past few decades have caused the great concern related to the future scarcity of clean freshwater and therefore it makes the importance of monitoring dissolved oxygen concentration as a barometer for river health [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Water quality is an indicator that represents the current state of the water resources for particular purposes (Kamarudin et al, 2019;Wahab et al, 2019;Wan Mohtar, Abdul Maulud, Muhammad, Sharil, & Yaseen, 2019). One of the water quality parameters that is often taken seriously in the agricultural industry is salinity (Ahmed & Haider, 2014;Khanom, 2016).…”
Section: Introductionmentioning
confidence: 99%